Short-term exercise combined with Acipimox administration induces an increase in plasma ACTH and its subsequent fall in the recovery phase in bulimic women - Smitka, Kvido; Papezova, Hana; Vondra, Karel; Hill, Martin; Hainer, Vojtech; Nedvidkova, Jara (Regulatory peptides, 2013)
OBJECTIVE: Free fatty acids (FFA)-adrenocorticotropin (ACTH) feedback loop between adipose tissue and the hypothalamic-pituitary centers in the brain has been suggested to be affected by the exercise and by administration of anti-lipolytic drugs. Also leptin may be affected by exercise. Dysfunction of FFA-leptin-ACTH secretion might be involved in binge eating and subsequent purging as is the case in bulimia nervosa (BN). METHODS: In the present single-blind, randomized study, we explored responses of plasma ACTH, leptin and FFA concentrations to exercise (45 min, 2 W/kg of lean body mass [LBM]) with Acipimox (Aci), an anti-lipolytic nicotinic acid analog, or placebo randomly received in nine women with BN and nine healthy women. RESULTS: The exercise with Aci administration resulted in plasma ACTH (p<0.001) and leptin increase higher in BN patients and a decrease in the plasma FFA levels in both groups. The falling of plasma ACTH (p<0.01) levels in the post-exercise recovering phase (90-minute) with Aci administration is more expressed in BN patients. The exercise induced an increase in plasma ACTH (p<0.05) and FFA levels and a decrease in the plasma leptin level in both groups. CONCLUSIONS: We demonstrated that the Aci-induced elevation in plasma ACTH (p<0.001) levels after the exercise higher in BN patients and that the falling of plasma ACTH (p<0.01) levels in the post-exercise recovering phase (90-minute) with Aci administration is suppressed only in BN patients, while Aci increased plasma leptin levels in this recovering phase more in BN patients. Therefore, these observations led us to suggesting that FFA-leptin-ACTH are involved in the dysregulation of neuroendocrine profile in this syndrome and that Aci affects a FFA-independent mechanism. In conclusion, Aci can be considered acceptable in the treatment of eating disorders, and it may also serve as an alternative low-dose dexamethasone suppression test (LDDST) in these patients. TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12612000309886.
Keywords: dospělí; adrenokortikotropní hormon; Pyrazines; Single-Blind Method; bulimia; Adrenocorticotropic Hormone; lidé; Female; jednoduchá slepá metoda; cvičení; Exercise; pyraziny; Adult; Bulimia; ženské pohlaví; Humans